In Vitro Antimalarial Susceptibility of Plasmodium falciparum and Plasmodium berghei Isolates to Selected Antimalarial Agents, Column Chromatographic Subfractions of Glyphaea brevis Leaves Extract and FTIR and GCNS of SF8 - Tayo Micheal Anjuwon,; Joseph Olorunmola Ehinmidu,; Kola Matthew Anigo,; Dorcas Bolanle James, (Tropical Life Sciences Research, 2023)
Malaria still remains a life-threatening parasitic disease with universal targets set for control and elimination. This study aimed to evaluate the in vitro antimalarial susceptibility of Plasmodium falciparum isolates and Plasmodium berghei to selected antimalarial agents and column chromatographic subfractions of Glyphaea brevis leaves extract and FTIR and GCMS of SF8. Trager and Jensen as well as World Health Organisation (WHO) standardised in vitro micro-test system methods were used to determine susceptibility on the patients’ blood samples; Column chromatographic procedure was carried out to obtain 11 pooled fractions; FTIR and GCMS were used to determine functional groups and phytochemicals respectively. In vitro anti-plasmodial activity against P. falciparum clinical isolates had IC50 range of 1.03 ?g/mL–7.63 ?g/mL while their IC50 against P. berghei ranges from 4.32 ?g/mL–7.89 ?g/mL. Subfraction 8 (SF8) had the least IC50 of 4.32 ?g/mL. The FTIR spectrum showed the presence of isoprenoid, alcohol, phenol, alkane, alkenes, ester, carboxylic acids, aromatics and nitro compounds while GCMS identified dodecanoic acid, methyl ester; carotol; hexadecanoic acid, methyl ester; 9-octadecenoic acid (Z)-, methyl ester (oleic acid); methyl stearate; heptadecanoic acid, 16-methyl-, methyl ester; all with their antimalarial reported activities. In conclusion, G. brevis has a great potential for drug development against malaria parasite since it inhibited schizont growth and possesses phytocompounds with antimalarial report.